The extent and distribution of salt-affected soils in sub-Saharan Africa from 1970 to the present: a review of the current state of knowledge - Mwesige, Finias Fidelis (Frontiers in Soil Science, 2025)
IntroductionSalt-affected soils are a global issue, affecting 1 billion hectares worldwide, including 80 million hectares in Africa. In sub-Saharan Africa (SSA), these soils originate from marine, geological, and hydrogeological sources, as well as human activities and arid climatic condition-induced salinization.MethodsThis systematic review, conducted using the PRISMA framework, provides an in-depth analysis of salt-affected soils in SSA from 1970 to the present. It highlights historical trends and emerging patterns of salinization in the region.Results and DiscussionThe review estimates that 65.6 million hectares of land in SSA are salt-affected, with key hotspots in coastal zones, river deltas like the Nile Delta, and arid areas with intensive irrigation. Generally, the coastal areas of Eastern Africa, Southwest Africa, and the West African and inland areas of the Nile Delta and Lake Chad Basin are the most vulnerable. Ethiopia is the most affected country, with 11 million hectares affected, primarily due to poor irrigation and drainage infrastructure. The study also highlights research gaps, revealing that coastal countries such as Senegal, Tanzania, and Kenya are better studied than inland areas like Chad and Mali. The in-depth review found that available estimates of salt-affected soils heavily rely on the FAO report of 1988, based on Solonchaks (saline soils) and Solonetz (sodic soils). This report was produced from the FAO Soil Map of the World at a scale of 1:5,000,000, which was created between 1970 and 1981. Due to its coarse resolution, high generalization, and environmental changes that have occurred over the decades, it may be considered outdated, presenting the need for updated data. The creation of digital fine-scale maps by integrating field and laboratory data, as well as soil data from FAO Soil Map of the World, HWSD, and WoSIS databases with remote sensing data, is highly suggested in this regard. Saline agriculture utilizing brackish water and salt-tolerant crops, improved salinity detection and monitoring, improved irrigation practices, application of gypsum and organic amendments (e.g., pressmud), and phytoremediation with halophytes are recommended. The study projects that these efforts could double agriculturally yields in affected areas, improving food security and economic resilience.